Political Violence and the Construction of National Identity in Latin America - Lambert, Peter. author. aut Link
XII, 245 p.
Keywords: This topical volume seeks to analyze the intimate but under-studied relationship between the construction of national identity in Latin America, and the violent struggle for political power that has defined Latin American history since independence. The result is an original, fascinating contribution to an increasingly important field of study.